Sustainable Halal Tourism Regulation Based on Local Wisdom in Indonesia and Uzbekistan - Jaelani, Abdul Kadir; Reza Octavia Kusumaningtyas; Sarjiyanto, Sarjiyanto; Bobur Sobirov (Lembaga Contrarius Indonesia, 2025)
Halal tourism plays a pivotal role in driving economic growth, particularly in countries with significant Muslim populations. However, the absence of comprehensive and harmonized regulatory frameworks remains a critical legal gap in advancing sustainable halal tourism. This research aims to construct a model of sustainable halal tourism regulation grounded in local wisdom by conducting a comparative normative legal study between Indonesia and Uzbekistan. Employing a conceptual, legislative, and comparative approach, the study reveals several key findings. First, in Indonesia, regulatory ambiguity and inconsistency exist regarding the definition and implementation of halal tourism, resulting in fragmented policies across regions. Central government regulations remain limited, while decentralization efforts have yet to empower local governments effectively. The minimal involvement of local authorities and communities in formulating halal tourism policies represents a significant shortfall, especially when local wisdom should be at the center of sustainable tourism development. Second, in contrast, Uzbekistan has developed a more integrated approach where sustainable tourism policies emphasize environmental preservation and cultural heritage, aligning more closely with the principles of halal tourism. Uzbekistan's model demonstrates the potential for integrating local values into national tourism policies as a foundation for sustainability. Third, the findings underscore the urgency for Indonesia to harmonize its halal tourism regulatory framework by integrating local wisdom and increasing the participatory role of local communities. A culturally contextualized legal approach is essential to ensure the long-term sustainability, legitimacy, and community acceptance of halal tourism practices.